PERANCANGAN APLIKASI PENDUKUNG KEPUTUSAN PENENTUAN PASANGAN TERBAIK DALAM PANDANGAN ISLAM DENGAN METODE AHP - Dwi Suci Anggraini (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2018)
Couples / soul mates have been determined by God the Almighty, humans are created in pairs and all humans must have been determined to live mate depending on the efforts of the man himself. Because of that we as human beings who want to endeavor and strive.         Therefore, a Decision Support System (DSS) is needed which can overcome problems in choosing the best partner. The method used in the Decision Support System (SPK) is the Analytical Hierarchy Process (AHP) method because it is appropriate for the decision-making process and can determine the weight value of each attribute, then proceed with a ranking process that will select the best alternative from a number of the best alternatives.                 Islam provides solutions and signs in choosing a mate, one of which is endeavor. Efforts and praying to Allah SWT in this way are good and true Decision Making.Keywords: SPK, AHP, Pair, Best